Fitness sharing ApplicationFor diversity Control with Evolutionary Algorithm To ResolveTravelling Salesman problem (TSP) - Feri susilawati; Taufik A. Gani2; Yuwaldi Away (J-Innovation, 2016)
To send a messages a courier (salesman) Cost much time and money. Thus it become a problem to optimizing in searching the shortest route that called as Traveling Salesman’s Problem (TSP).which a salesman should delivering letters tomany places, each place must be visited in single time and then back to the starting place. The optimizing problem that should be reached isthe shorter route and the minimum cost. In this research, Fitness Sharing with Evolutionary Algorithm (EA) proposed to minimize ethe route and individual convergent (diversity) in the population of each generation, before reaching the optimum point. In the result it will produce a computation time with the minimum route.